Clinical severity scores as a guide for prediction of initial treatment responses in pemphigus and pemphigoid patients. Issue 2 (31st July 2022) - Tanaka, Ryo; Kurihara, Yuichi; Egami, Shohei; Saito, Yasuko; Ouchi, Takeshi; Funakoshi, Takeru; Takahashi, Hayato; Umegaki‐Arao, Noriko; Kubo, Akiharu; Tanikawa, Akiko; Amagai, Masayuki; Yamagami, Jun
Abstract: Pemphigus and pemphigoid are autoimmune blistering diseases that affect mucosa and skin. Several clinical scoring systems, including the pemphigus disease area index (PDAI) and the bullous pemphigoid disease area index (BPDAI), have been validated for managing disease activity and severity. Current guidelines recommend that treatment response be evaluated with clinical scores and that additional second‐line therapies be considered if initial treatment is insufficient for disease control. However, there have been few studies analyzing correlations between PDAI/BPDAI transitions and initial treatment effects. To investigate whether PDAI/BPDAI transitions during the treatment initiation phase correlate with initial treatment responses and whether such information can be used as a guide for necessary additional treatment, we retrospectively analyzed 67 pemphigus patients and 47 pemphigoid patients who received initial treatment at Keio University between 2012 and 2018. The clinical symptoms were evaluated weekly with PDAI/BPDAI. The patients were divided into two groups: in group A, disease was controlled only with oral corticosteroids and immunosuppressants (initial treatment), whereas in group B additional therapies were required due to insufficient responses. In pemphigus, the PDAI ratio of day 7/day 0 was significantly reduced in group A compared to group B (0.548 vs 0.761, P < 0.01) after initial treatment had started. In pemphigoid, the ratios of day 7/day 0 of BPDAI (erosion/blister) and BPDAI (urticaria/erythema) significantly decreased in group A compared to group B (0.565 vs 0.901 and 0.350 vs 0.760, respectively, P < 0.05). Receiver operating characteristic analyses on PDAI, BPDAI (erosion/blister) and BPDAI (urticaria/erythema) revealed that the cut‐off values in the ratios of day 7/day 0 were 0.762, 0.675, and 0.568, respectively. Our results suggest that PDAI/BPDAI transitions during the initial phase of the treatments may be useful to predict the outcome of the treatment provided and the necessity of additional therapies to achieve disease control.